Nanotherapeutics Overcoming the Blood-Brain Barrier for Glioblastoma Treatment - Tang, Lin; Feng, Yicheng; Gao, Sai; Mu, Qingchun; Liu, Chaoyong (Frontiers in Pharmacology, 2021)
Glioblastoma multiforme (GBM) is the most common malignant primary brain tumor with a poor prognosis. The current standard treatment regimen represented by temozolomide/radiotherapy has an average survival time of 14.6 months, while the 5-year survival rate is still less than 5%. New therapeutics are still needed to improve the therapeutic outcome of glioblastoma treatment. The blood-brain barrier (BBB) is the main barrier that prevents therapeutic drugs from reaching the brain. Nanotechnologies that enable drug delivery across the BBB hold great promise for the treatment of glioblastoma. This review will summarize the various drug delivery systems used to treat glioma and focus on their approaches for overcoming the blood-brain barrier to enhance the accumulation of small molecules, protein and gene drugs, etc. in the brain.